Fuzheng Xiaoai Decoction 1 ameliorated cancer cachexia-induced muscle atrophy via Akt-mTOR pathway. (1st March 2023) - Cheng, Qiao-Qiao; Mao, Shi-Long; Yang, Li-Na; Chen, Li; Zhu, Jin-Zhi; Liu, Xuan; Hou, An-Ji; Zhang, Rong-Rong
Abstract: Ethnopharmacological relevance: Fuzheng Xiaoai Decoction 1 (FZXAD1) is a clinical experience prescription for the treatment of cancer patients at an advanced stage. FZXAD1 has been used for more than 10 years in the clinic and can effectively improve the deficiency syndrome of cancer patients. However, its mechanisms need further clarification. Aim of the study: To check the effects of FZXAD1 in colon 26 (C26) cancer cachexia mice and try to clarify the mechanisms of FZXAD1 in ameliorating cancer cachexia symptoms. Materials and methods: An animal model of cancer cachexia was constructed with male BALB/c mice bearing C26 tumor cells. Food intake, body weight and tumor size were measured daily during the animal experiment. Tissue samples in different groups including tumor and gastrocnemius muscle, were dissected and weighed at the end of the assay. Serum biochemical indicators such as total protein (TP), glucose (GLU) and alkaline phosphatase (ALP) were also detected. Network pharmacology-based analysis predicted the possible targets and signaling pathways involved in the effects of FZXAD1 on cancer cachexia therapy. Western blotting assays of the gastrocnemius muscle tissues from C26 tumor-bearing mice were then used to confirm the predicted possible targets of FZXAD1. Results: The results of animal experiments showed that FZXAD1 could ameliorate cancer cachexia by alleviating the muscle wasting as well as kidney atrophy and increasing the body weight of cancer cachexia mice. AKT1, MTOR, MAPK3, HIF1A and MAPK1 were predicted as the core targets of FZXAD1. Western blotting confirmed the prediction that FZXAD1 increased the expression levels of phosphorylated Akt and mTOR in the muscle tissues. In addition, FZXAD1 treatment obviously ameliorated the increased levels of HIF-1α and phosphorylated Erk1/2 in C26 tumor-bearing mice. Conclusion: FZXAD1 effectively ameliorated cancer cachexia in an animal model of mice, which is consistent with its efficacy in the treatment of cancer patients. The mechanisms of FZXAD1 might be mainly based on its alleviating effects on muscle atrophy by activating the Akt-mTOR pathway and thus helping to maintain body weight. Graphical abstract: Image 1 Highlights: Finding candidate drugs for cancer cachexia treatment based on alleviating deficiency syndrome is significance. Fuzheng Xiaoai Decoction 1 kept body weight of cancer cachexia mice by alleviating muscle wasting as well as kidney atrophy. Akt-mTOR pathway was suppressed during cancer cachexia. Fuzheng Xiaoai Decoction 1 ameliorated cancer cachexia by activating Akt-mTOR pathway and thus alleviating muscle atrophy.